Big data e sedimentazioni etiche. La memoria tra il simbolico e il sub-simbolico - Pisano, Aldo (Mechane, 2020)
The aim of this paper is to analyze the concept of memory from an ethical perspective and in relation to AI e and Big Data. So, we’ll focus on a basical difference between “factual” memory and “value” memory: the first one linked to the “quantity” of episodes, the second one to the “quality” of episodes collected by the subject. In the first case, we’re close to machines’ cognitive structure, in the second case we’re close to human’s cognitive structure. According to the ethical perspective, it is more important the role of “quality” criterion than the “quantity” one. This applies both to individual and collective memory. If we assume the memory’s paradigma as a simple collection of data, this have critical implications in ethical development of the moral subject. So, memory and individual (or social) life will crush on a computational state.